Underlying causes and stability of intraspecific variation in behaviour of microtine rodents - Šíchová, Klára (Jihočeská univerzita, 2017)
Two crucial issues related to personality in non-human animals have been identified: firstly, the underlying 'causes' of personality and,secondly, the stability of behavioural repertoires (essentially the defining feature of personality) have both been the subject of long-standing debate. This thesis is focused on investigating stable inter- and intra- individual differences in the behaviour of wildcaught bank voles, Myodes glareolus (that varied according to mtDNA type), and in common voles, Microtus arvalis. The first study, using wild voles, revealed empirical evidence about the effects of sex and mtDNA type on individual differences in basal metabolic rate and in behaviour in the open field which provides measures of approach and avoidance (here, generically termed 'proactivity') and which relate to several theoretical conceptualisations of animal personality. The second study demonstrated the presence of stable individual differences in reactions to exposure to open field test and radial maze in common voles, which were shaped by the social environment and in turn, related to cognitive efficiency. The same species was used in the third study documenting the distinct temporal patterns of behavioural plasticity that manifested over repeated exposures to the open field test. We suggest that this distinct temporal patterning in habituation, whilst it varied over time, was predictable in nature and therefore a reflection of a stable underlying personality. To conclude, this body of thesis work draws together a number of influencing factors, and considers their contribution to animal personality.
Underlying causes and stability of intraspecific variation in behaviour of microtine rodents
Keywords: animal personality; behavioural plasticity; Open Field test; common vole; repeated testing; animal personality; behavioural plasticity; Open Field test; common vole; repeated testing